Labor market news and expectations about jobs & earnings - Bernhard Schmidpeter (Johannes Kepler University of Linz, Department of Economics, 2023)
Little is known about how workers update expectations about job search and earnings when exposed to labor market news. To identify the impact of news on expectations, I exploit Foxconn's unexpected announcement to build a manufacturing plant in Racine County. Exposure to positive news leads to an increase in expected salary growth at the current firm. Individuals also revise their expectations about outside offers upward, anchoring their beliefs to Foxconn's announced wages. They act on their updated beliefs with a small increase in current consumption. Negative news from a scaled-down plan leads to a revision of expectations back toward baseline.
Keywords: C33; D84; E24; J31; J63; 330; beliefs formation; wage expectations; outside options; consumption